The Effect of Service Quality toward Customer Satisfaction in a Sharia Pawnshop (Case Study on a Sharia Pawnshop in Jambi Province) - Busriadi Busriadi; Rahman Arifin (AL-FALAH : Journal of Islamic Economics, 2021)
Purpose: This research analyzes the business phenomenon of PT. Pegadaian Syariah (Persero) Tbk. in Jambi province, in which the problem is how to build customer satisfaction to achieve the company goal. This research is designed to analyze the effect of service quality on customer satisfaction. This research aims to find answers to the flow of service quality performance. In addition, the modeling in this study also aims to provide a critical understanding of the concept and measurement of customer relationship management.Design/Method/Approach: This research used a descriptive analysis approach and a quantitative method to test the variables by using hypothesis testing. The research subjects were 110 customers of PT. Pegadaian Syariah (Persero) Tbk. of Jambi Province. To analyze the data, researchers used the Structural Equation Model (SEM) by using Amos 22 computer program.Findings: The results showed that service quality had a positive and significant effect on customer satisfaction. This study provides a contribution that strengthens the justification of previous research in which this research develops the effect of service quality by expanding the study on customer satisfaction.Originality/Values: The novelty of the study is identified from the issue which is studied consistently and the place of the research.